NESTLE SCANDALS, NEGATIVE IMPACT OF CONFLICTS TO BRAND PRESTIGE (Academicia Globe: Inderscience Research, 2021)
“Nestle” is one of the most successful food company, which is well-known to the World. The current article will discuss dark sides of Nestle, in other words misconduct cases of Nestle. Human trafficking, illegal use of water resources, child labor, usage of price-fixing strategy are some of the main accusations against Nestle. Involvement in such misconducts, harms Nestle’s prestige and reputation, which will subsequently lead to decrease in sales and loosing customers. The current article studies these aspects and gives some conclusions on the basis of Nestle’s experience.